Do the Leadership Has an Impact toward Employee Performance at KUBE Hotel in Ubud? - Anak Agung Dhimas Dharmika Pemayun; Ni Desak Made Santi Diwyarthi; Clearesta Adinda (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
Employees play a crucial role in creating added value for a company through innovation, operational efficiency, and excellent customer service. Leadership factors have a significant role in determining the success of an organization's goals in building good employee performance. Motivated by several employee performance issues, this research aims to examine how the leadership style applied at Hotel KUBE, influences employee performance. The data collected in this study consist of questionnaire responses from a sample of 57 participants using purposive sampling. Purposive sampling is a non-probability sampling technique in which the researcher selects samples based on specific considerations or objectives deemed relevant to the study. The sample selection is carried out intentionally to ensure that the samples possess certain characteristics required to answer the research questions. According to the theories of Sugiyono (2017) and Etikan and Bala (2020), purposive sampling is used when researchers have specific criteria or considerations in selecting research subjects, so the selected subjects are expected to provide in-depth information. Data collection utilized Likert scale questionnaires. The data analysis technique employed simple linear regression analysis, t-test, and coefficient of determination test. Based on the analysis and discussion, it can be concluded that the Leadership Style does not have a significant influence on employee performance at Hotel KUBE, with an R2 value of 0.082 or 8.2%. The calculated t-value of -2.213 is smaller than the t-table value of 1.673, and the significance value is <α = 0.031 < 0.005.